PENGARUH TEKOLOGI INFORMASI, SISTEM INFORMASI AKUNTANSI MANAJEMEN, DAN PENGENDALIAN INTERNAL TERHADAP KINERJA KOPERASI - Purba, Sahala; Sitohang, Santy Aji (Jurnal Akuntansi, 2024)
This research aims to determine whether Digital Technology, Management Accounting Systems, and Internal Control Systems influence Cooperative Performance at the CU Sondang Nauli Kabanjahe Savings and Loans Cooperative. The type of research used is quantitative descriptive. The population in this study consisted of all administrators and employees at the CU Sondang Nauli Kabanjahe Savings and Loans Cooperative, with a sample of 87 people, including administrators and employees. The data type used in this research is quantitative data, and the primary data source is primary data. Data collection techniques using questionnaires. The data analysis technique used in this research is descriptive statistics. In testing the quality of primary data, researchers conducted validity and reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis tests using the SPSS 26 application. The research shows that, individually, Digital Technology the Application of Accounting and Control Information Systems positively and significantly affects Cooperative Performance.